ZZ/ZW sex chromosome system in the endangered fish Lignobrycon myersi Miranda-Ribeiro, 1956 (Teleostei, Characiformes, Triportheidae) - Rodrigues, Alexandre dos Santos; Medrado, Aline Souza; Diniz, Débora; Oliveira, Claudio [UNESP]; Affonso, Paulo Roberto Antunes de Mello (Pensoft Publishers, 2016)
Lignobrycon myersi is an endemic fish species from a few coastal rivers in northeastern Brazil. Based on molecular evidence, L. myersi and genera Triportheus Cope, 1872, Agoniates Müller & Troschel, 1845, Clupeacharax Pearson, 1924 and Engraulisoma Castro, 1981 were placed in the family Triportheidae. In the present work, we report the first cytogenetic data for L. myersi to test the hypothesis that Lignobrycon and Triportheus are closely related. Studied specimens presented 2n=52 with 28 metacentric (m), 18 submetacentric (sm) and six subtelocentric (st) chromosomes for males and 27 m, 19 sm and 6 st for females, characterizing a ZZ/ZW sex chromosome system. The Z chromosome corresponds to the largest chromosome in karyotype while the W is about 50% smaller than the Z and largely heterochromatic. Terminal nucleolus organizer regions, GC-rich sites and 18S rDNA signals were detected on pair 14. However, additional 18S rDNA sites were observed in the W chromosome. The 5S rDNA was mainly detected on long arms of pair 7. The apparent synapomorphic chromosomal traits of Triportheus and L. myersi reinforce their close phylogenetic relationship, suggesting that the ZZ/ZW chromosome system in both genera has arisen before cladogenic events.
Keywords: Evolution; Female heterogamety; RDNA; Sex determination; Triportheus